Bloody Cartoons: Freedom of Expression and the Clash of Cultures - Films Media Group (2008)
In 2005, a handful of Danish cartoons sparked a worldwide debate over freedom of expression-and the freedom to express religious outrage. Was a violent Islamic backlash against caricatures of the prophet Mohammed justified? Can democracy and fundamentalism coexist in the global community? This program travels to Lebanon, Iran, Syria, Qatar, and Turkey, as well as to France and Denmark, in search of answers. Viewers will encounter a wide array of perspectives from influential figures-such as Raed Hlayhel, the Danish Imam who moved to Lebanon to spearhead protests; Sheikh Yusef al-Qaradawi, the al-Jazeera Islamic televangelist who called for a "day of anger" against the cartoons; and leading staff members of newspapers that published them. (54 minutes).
fma39613
Mode of access: World Wide Web.
System requirements: Windows Media, etc.